Prevalência de alterações comportamentais em cães idosos - Svicero, Denis Jeronimo [UNESP]; Heckler, Marta Cristina Thomas [UNESP]; Amorim, Rogério Martins [UNESP] (FapUNIFESP (SciELO), 2017)
Owing to improvements in animal welfare, such as in nutrition, preventive medicine, and diagnostic tools, older dogs have become increasingly more prevalent than before. Unfortunately, there is an increasing number of dogs presenting behavioral changes correlated with this growth in the geriatric population. However, many of these owners consider these signs as normal for old age. This study aimed to determine the prevalence of clinical signs related with behavioral changes in the canine geriatric population admitted to the Veterinary Hospital of the Veterinary Medicine and Animal Science College of Universidade Estadual Paulista. The owners of 800 old dogs completed a questionnaire about disorientation, changes in social interaction, loss of training (house soiling), changes in the wake-sleep cycle, physical activity, memory, learning, consciousness, and perception. The results showed that the prevalence of behavioral changes in the canine geriatric population was 90.7% of dogs that presented at least one of these behavioral changes, and 22.3% with at least six changes, and with changes in physical activity (58.5%) and loss of acquired training (30.2%) being the highest percentage groups that were reported by the owners. We concluded that the prevalence of behavioral changes related with aging in the canine geriatric population was high, and that it was important to include questions about behavioral changes during regular veterinary clinical appointments to identify these clinical signs earlier and investigate the possible causes of the cognitive impairment, including neurological diseases, such as Canine Cognitive Dysfunction Syndrome.
Prevalence of behavioral changes in senile dogs
Keywords: Behavioral changes; Cognitive dysfunction; Neurology; Old dogs